Counterinsurgency Scorecard Update Afghanistan in Early 2015 Relative to Insurgencies Since World War II - Paul, Christopher (RAND Corporation, 2016)
A key finding of previous RAND research on insurgencies worldwide since World War II was that an overall score on a scorecard of 15 equally weighted good and 11 equally weighted bad counterinsurgency factors and practices distinguished conflicts' historical outcomes. Using the scorecard approach and an expert elicitation exercise, a RAND study sought to extend the findings to the case of Afghanistan in 2015.